1990
DOI: 10.1007/bf00120461
|View full text |Cite
|
Sign up to set email alerts
|

Diabatic wind speed profiles in coastal regions: Comparison of an internal boundary layer (IBL) model with observations

Abstract: A model is presented to transform wind speed observations at a single height over sea or near the coast to any possible location and height in a topographic flat coastal region (up to distances of about 5 km from the coast and up to heights of IO0 m). Only moderate and strong winds from the sea are considered, which are particularly important for wind energy applications. The model, called 'diabatic coast model', which is based on the well known internal boundary layer (IBL) concept and Monin-Obukhov similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…The latter is responsible for the cyclonic filling due to vertical wind and ventilation on the ABL top (Beare, ). Beljaars and Viterbo () showed that, in order to have good score for cyclonic filling, an enhanced mixing function was necessary. Contrary to their results, we show that the new GWDSBL parametrization is able to accurately reproduce the CCP of cyclones due to enhanced momentum drag from gravity wave dissipation within the SBL.…”
Section: Experimental Results For the Model Run 2–10 January 2012mentioning
confidence: 99%
See 3 more Smart Citations
“…The latter is responsible for the cyclonic filling due to vertical wind and ventilation on the ABL top (Beare, ). Beljaars and Viterbo () showed that, in order to have good score for cyclonic filling, an enhanced mixing function was necessary. Contrary to their results, we show that the new GWDSBL parametrization is able to accurately reproduce the CCP of cyclones due to enhanced momentum drag from gravity wave dissipation within the SBL.…”
Section: Experimental Results For the Model Run 2–10 January 2012mentioning
confidence: 99%
“…The near‐surface temperature in the SBL depends on the amount of diffusion that we represent in each scheme. Beljaars and Viterbo () showed that the enhanced mixing functions, similar to the mixing function of our LT set‐up, have higher near‐surface temperatures than traditional ST mixing functions due to enhanced mixing. This results in a smaller negative bias in the 2 m temperature for LT mixing functions.…”
Section: Experimental Results For All 16 Model Runsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is often caused by heterogeneity in surface roughness, the effect of which is discussed in terms of the morphology of the land use condition 4–7 . In addition, thermal heterogeneity often arises owing to differing surface albedo and heat capacities at the land–sea interface 8–15 . This has occasionally been a focal WT issue under stably stratified conditions in the northwestern European region 13,14 .…”
Section: Introductionmentioning
confidence: 99%